2019
DOI: 10.1007/s12040-019-1236-0
|View full text |Cite
|
Sign up to set email alerts
|

Stable chlorine isotopes in saline springs from the Nangqen basin, Qinghai–Tibet Plateau: Brine genesis and evolution

Abstract: Chlorine isotopes can be used to study the evolution of different fluids, sources and the causes of various related deposits. In this study, Cl concentrations and chlorine isotope (d 37 Cl, IAEA ISL-354 NaCl standard) values were determined for brine samples from Nangqen basin, located on the southern boundary of the Qinghai-Tibet plateau to study the source and the processes of these saline springs. The results demonstrated that the saline springs are distributed around a fault or fault zone, with a high aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Figure 6 shows that the Bahadurkhel and Karrak samples are mostly characterized by rather constant δ 37 Cl ∼−0.2‰ but varying Br/Cl ratios, whereas the Jatta samples display somewhat positive δ 37 Cl values with considerably constant Br/Cl ratios. This may be explained by frequent and multiple dissolution and precipitation processes as Br contents decline with successive recycling processes (Eggenkamp et al, 2019b;Han et al, 2019). It also indicated that the basin was disconnected from the main water reservoir (i.e.…”
Section: Halite Geochemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 6 shows that the Bahadurkhel and Karrak samples are mostly characterized by rather constant δ 37 Cl ∼−0.2‰ but varying Br/Cl ratios, whereas the Jatta samples display somewhat positive δ 37 Cl values with considerably constant Br/Cl ratios. This may be explained by frequent and multiple dissolution and precipitation processes as Br contents decline with successive recycling processes (Eggenkamp et al, 2019b;Han et al, 2019). It also indicated that the basin was disconnected from the main water reservoir (i.e.…”
Section: Halite Geochemistrymentioning
confidence: 99%
“…Brennan et al (2013) reported Br − concentrations of 11 ppm for halites from the Catalan sub-basin, whereas Moretto (1986) reported Br − concentrations of 10 ppm for the Bresse Basin. The Eocene salts from Bhadur Khel have lower Br − concentrations compared to the other Paleogene and Neogene basins (1.3-2.37 ppm) that indicate an entry of non-marine water (Shouakar-Stash, 2008) or the dissolution or recycling of ancient marine halite (Brennan et al, 2013;Han et al, 2019;Eggenkamp et al, 2019b). The study of the Cl/Br ratio has proved to be one of the most effective and sensitive indexes when defining the geological environment, brine concentrations and the depositional stages associated to the brine evaporation process (e.g.…”
Section: Halite Geochemistrymentioning
confidence: 99%
See 2 more Smart Citations